Impact style of the changeable resistance in the development some of physical & functional changes for the National team for the badminton - Abeer Dakhil Hatim (الرياضة المعاصرة)
The most better activities  of sports that Badminton  which develop the physical fitness , and the game needs the competition and more running and jumping  as well as , the fast  reaction and balance movement to association between the eyes and hands , hereby it needs to high felling and moving , specially when practice the extensive bits in the jumping or supporting , the player should be recognized the time of the ball when sending or receiving from the adversary .